Carbon Border Adjustment Mechanism: Between Climate Target and Climate Justice - Hikmatul Ula (Fakultas Hukum Universitas Islam Indonesia, 2026)
The Carbon Border Adjustment Mechanism (CBAM) is a new climate policy instrument adopted by the European Union, meant to reduce industrial carbon emissions and protect against carbon leakage. Through this mechanism, imported goods into the EU will be subjected to an equivalent carbon cost up to the standards imposed on domestic producers. Therefore, in one aspect, CBAM becomes an instrumental policy for net zero emission targets and green economy transformation; but on the other hand, it has been criticized as a unilateral measure that may also discriminate against developing countries. Hence, this paper discusses CBAM under international trade law and environmental law perspectives while assessing its consistency with climate justice and just transition principles. The findings suggest that while CBAM may be normatively justified as part of the climate mitigation effort, practically speaking it risks exacerbating global inequality if not accompanied by mechanisms for compensation, technology transfer, and recognition of the principle of common but differentiated responsibilities (CBDR) in the existing, less inclusive multilateralism. A more inclusive multilateralism is missing from ensuring that global climate policies are not only technically effective but also socially just.